Security Studies: Towards a Reformational Approach - Freire, Lucas G. (Philosophia reformata, 2016)
How can reformational philosophy help us reconceptualise the notion of security? In the field of Security Studies, theoretical isms abound, each of them rooted in a different philosophical tradition. One of these approaches, “securitization theory”, portrays security in connection to five “sectors” that seem to reflect some of the basic aspects of the cosmos analysed by reformational philosophy. I consider the potential of this theory in an initial attempt to introduce a reformational approach to Security Studies. I also briefly consider some of its shortcomings. Finally, I reflect on the basic elements of a reformational notion of security. At this stage I am not offering a new theory of security but merely beginning to sketch a new concept of security in light of reformational philosophy.